2014
DOI: 10.1080/01635581.2014.948213
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Total Homocysteine Level in Association With Folate, Pyridoxine, and Cobalamin Status Among Iranian Primary Breast Cancer Patients

Abstract: Recently the elevated plasma total homocysteine (tHcy) concentration has been concerned as the secondary feature of tumoral proliferation and enhances the likelihood of thrombogenesis in cancer patients. The objective of this study was to determine the associations between folate, cobalamin, and pyridoxine with fasting plasma tHcy concentration in breast cancer (BC) patients. The intake levels of nutrients were assessed using a validated food frequency questionnaire in 141 newly diagnosed BC patients. The plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…The present FFQ was validated for 136 food items to ascertain relatively precise estimates of nutrients in one-carbon metabolism [16,[21][22][23]; however, most previous studies having inconclusive results neglected to administer a validated FFQ or did not validate the FFQ for their own populations. The validity test is important because there is an overriding concern about misclassification of one-carbon nutrients from generally used questionnaires.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present FFQ was validated for 136 food items to ascertain relatively precise estimates of nutrients in one-carbon metabolism [16,[21][22][23]; however, most previous studies having inconclusive results neglected to administer a validated FFQ or did not validate the FFQ for their own populations. The validity test is important because there is an overriding concern about misclassification of one-carbon nutrients from generally used questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence addresses the links between onecarbon metabolism and aberrant DNA methylation [13,14]. Folate as 5-methyl-tetrahydrofolate (5-methyl-THF) is a methyl donor that regenerates methionine from homocysteine to support S-adenosylmethionine (SAM)-dependent biological transmethylation reactions [15,16]. Nevertheless, some randomized clinical trials have shown that folate supplementation may increase genomic methylation density, and insufficient folate intake may play a role in defected methylation maintenance regulating upstreams of some genes [9,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary data were collected using a validated semi-quantitative 136-item food frequency questionnaire (FFQ) (31)(32)(33)(34). Portion sizes and frequency of consumption were requested for each food item on a daily, weekly, monthly, or yearly basis.…”
Section: Nutritional Datamentioning
confidence: 99%
“…Hyperhomocysteinemia is a condition where serum HCY level is above 15 µmol/L [8]. When any one of the Vitamin B 12 , Vitamin B 6 , and folic acid deficiency occurs, plasma HCY levels increase in the body [9].…”
Section: Reference Rangementioning
confidence: 99%